Genome Assembly of Arctica islandica, the Longest-Lived Non-Colonial Animal Species - Glenn S. Gerhard; John B. Allard; Scott Kaniper; Dorret Lynch; Hayan Lee; Sudhir Kumar (Animals, 2025)
We report the first high-quality genome-wide assembly for Arctica islandica, the longest-lived non-colonial species, with a reported maximum life span of 507 years. The genome was assembled using short- and long-read DNA sequencing and RNA sequencing of four tissues. All assessment approaches indicated that the assembled genome is complete, contiguous, and accurate. The genome size is estimated at 1781.15 million base pairs (Mbps) with a coverage of 247.8×. The heterozygous rate was 1.15% and the repeat content 67.66%. Genome completeness evaluated by complete BUSCOs was 92.7%. The non-redundant gene set consisted of 39,509 genes with an average transcript length of 15,429 bp. More than 98% of the genes could be annotated across databases. Predicted non-coding RNAs included 801 miRNAs, 11,114 tRNAs, 909 rRNAs, and 349 snRNAs. The Arctica islandica genome, along with the assembly of genomes from other clam species, sets the stage for elucidating the molecular basis for the convergence of extreme longevity across these bivalve species.